The Image of Witch in the Documents of the Salem Witch-Trial - Leionis A. Van Khaaske (Publishing house "Sreda", 2021)
The article attempts to reconstruct the image of a witch based on the interrogation records of those accused of witchcraft during the Salem trial (Massachusetts, North America, 1692) and related materials. The subject of research is the phenomenon of prosecution on those accused of witchcraft. The source base are the records of the Salem process, transcribed and published in 1977, as well as a number of documentary testimonies of witnesses, speaking from a puritanical viewpoint. The article examines the features of the mythological worldview of traditional society, dictated by the belief in supernatural influence (witchcraft). After analyzing the interrogation records of the first accused during this trial and considering a number of their biographical data, the author comes to the conclusion that the situation demonstrated by this trial is paradoxical: in fact, arbitrary people are subjected to persecution, and the reconstruction of the image of a witch that could underlie such accusations, does not seem possible. The author's conclusions are essential for the study of both the phenomenon of witch-trials and the mentality of traditional society. This article was conducted from an imagological perspective relevant to modern social studies.